Radiation from hot accretion flows onto black holes - Gutiérrez, Eduardo Mario (2020)
The hot accretion flows upon black holes are usually optically thin two-temperature plasmas inwhich electrons can achieve temperatures up to 1010 K, producing radiation via synchrotron, bremsstrahlung andinverse Compton, and the ions can reach temperatures up to 1012 K. The hottest ions might produce gammaemission through proton-proton interactions. In this work, we considered a particular model of a hot accretionflow and estimate the spectral energy distributions produced by both species of particles.